Can Viewing a Video of Colposcopic Examination Improve Patient Knowledge and Satisfaction with the Procedure? A Prospective Randomized Controlled Trial - Sasiwan Suthasmalee; Teera Siwadune (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To evaluate whether viewing a video of a colposcopic examination can improve patient knowledge of the procedures involved. The secondary objectives involved evaluations of satisfaction with the procedure and of follow-up data when comparing the study group and the control group.Materials and Methods: In the prospective randomized controlled trial, 172 patients all referred for colposcopy for the first time were randomly spilt into two groups. Seven patients were excluded from further analyses, leaving 165 patients for evaluation. The control group (n=75) received the conventional information brochure, while the study group (n=90) also viewed the video. Each patient completed a questionnaire to evaluate patient knowledge and satisfaction both before and after treatment. Results: Viewing a video of colposcopy treatment can improve patient health education of the procedure. The study group had higher significant difference post-colposcopy knowledge scores than the control group (17.28 and 16.22, p < 0.05). However, after colposcopy the patients showed in averagely high satisfaction scores (> 8) and high follow up rate (> 87%), with no statistical significance in both groups. Conclusion: Viewing a video before colposcopy treatment increased patient knowledge scores but failed to significantly increase satisfaction and follow-up data.